An Analysis of Perception of MSMEs Toward Adoption of Digital Practices with Special Reference to Karnataka - Banu, Sameena (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : MSMEs are crucial for economic growth as they drive employment, innovation, exports, and inclusive regional development. The study’s main objective was to know the perception of MSMEs toward the adoption of digital practices. Methodology : The study was based on both primary and secondary sources of data. The primary data for the present study was collected through the structured questionnaire and interview method by using Google Forms and phone calls. It used the factor analysis tool to identify the factors that jointly contributed to the adoption of digital practices. We collected data from MSMEs in Karnataka through surveys. The study on the perception of digital practices among respondents included 20 factors under four components, such as information value, trustworthiness, cost-effectiveness, and business competitive advantage. Findings : It was found from the factor analysis that the business competitive advantage was the major force that largely influenced the adoption of digital practices. Practical Implications : The study recommended that MSMEs need to come forward to understand the importance of digital practices to improve efficiency in business operations. Policymakers and support organizations can leverage these insights to create enabling environments for MSMEs’ digital transformation by providing training programs, resources, and financial assistance tailored to their specific needs. Originality : By fostering a culture of innovation and adaptability, MSMEs can harness the full potential of digital technologies to enhance their market presence and drive sustainable growth.